Brain metastasis from prostate cancer: A review of the literature with an illustrative case. (December 2021) - Al-Salihi, Mohammed Maan; Al-Jebur, Maryam Sabah; Lozada-Martinez, Ivan David; Rahman, Md Moshiur; Rahman, Sabrina
Abstract: Introduction and importance: Brain metastasis of prostatic cancer is highly a rare condition. Its intracranial metastatic process and presentation are poorly understood and limited to case reports, making it challenging to detect and diagnose. We aim to highlight the rare case, brain metastasis of prostate cancer, and review the literature regarding the progress and therapies of prostatic cancer in the current era. The case of a prostate adenocarcinoma patient who acquired brain metastasis was outlined. In addition, we review the literature to discuss the main aspects of brain metastasis in prostate cancer. Case presentation: Herein, the patient was a 62-year-old male with metastatic prostate adenocarcinoma into the brain, which suffered from progressive language difficulties, mixed dysphasia, and right hemiparesis. Clinical discussion: Brain magnetic resonance imaging revealed a left frontoparietal mass, confirmed with an elevated PSA level. The group was resected, and after that, the patient was discharged with noticeable language and neurological improvement. Upon follow-up, after six months, a new asymptomatic left temporal lesion was observed and successfully treated with chemotherapy and radiotherapy. This case confirms that prostatic adenocarcinoma's possibility to spread into the brain. Conclusion: This report reviews the literature about prostate cancer brain metastasis, highlighting that although rare, it does occur and shouldn't be neglected, especially with the current progress in prostatic cancer therapies, which prolongs the patient's survival time, so those brain metastases out of prostatic cancer are expected to be a frequent clinical scenario. Therefore, follow-up of prostatic cancer male patients of 50 years old or more is necessary. Highlights: Brain metastasis of prostatic cancer is a rare condition & limited to case reports. It is possible that prostatic adenocarcinoma can spread into the brain. The follow-up of prostatic cancer male patients of 50 years old or more is necessary. Abstract : Key message: The milestone of treating the cerebral metastasis of prostate cancer is early detection, early management, and follow-up.